The Effect of the Combination of Coconut Water on the Chemical and Sensory Properties of Sweet Bread - Elsina Henderika Ohoiner; Meitycorfrida Mailoa; Syane Palijama (Jurnal Agrosilvopasture-Tech, 2022)
The study aimed to determine the appropriate concentration of coconut water for the production of sweetbreads with good chemical and organoleptic properties. The study used a complete design with a comparison of water and coconut water, 100% water, 75%:25%, 50%:50%, 25%:75%, and 100% coconut water. The results showed that the treatment of coconut water concentration of 100% produced the best sweetbread with chemical characteristics of 12.16% fat content, 11.01% protein content, 1.40% ash content, 55.05% carbohydrate content, and 20.35% moisture content. Panelists liked color (4.33), laroma (4.11), texture (4), taste (4.19), and overall likeness (4.38), while for hedonic quality, the bread had a brownish yellow color (3.63), a flavorful coconut water (3.41), a soft texture (3.98), and was sweet (3.64).